Smart intruder detector / Mohamad Syahir Naim Mohammad Razali, Nor Amira Ismail and Tengku Zuraini Tengku Sulaiman - Mohammad Razali, Mohamad Syahir Naim; Ismail, Nor Amira; Tengku Sulaiman, Tengku Zuraini (2013)
This smart intruder detector project is a system that allow the user and people surround to alert when intruders were enter the premises. This will help to reduce the crime case based on breaking houses. This system function when the detector on the door detect the motion of the door when it was opened. The system will alert the user by showing the light and the buzzer make loud sound. This system only can be shut down by the owner by the combination of switch.